Effects of hope promoting interventions based on religious beliefs on quality of life of patients with congestive heart failure and their families - Niloufar Binaei; Mahin Moeini; Masoumeh Sadeghi; Mostafa Najafi; Zahra Mohagheghian (Wolters Kluwer Medknow Publications, 2016)
Background: Heart failure is one of the most important and prevalent diseases that may have negative effects on the quality of life (QOL). Today, the promotion of QOL in patients with heart failure is important in nursing care programs. This research aimed to determine the efficacy of hope-promoting interventions based on religious beliefs on the QOL of patients with congestive heart failure (CHF). Materials and Methods: In this randomized clinical trial (IRCT2014100619413N1) conducted in Isfahan, Iran, 46 adult patients with CHF were selected and randomly assigned to study and control groups. Ferrans and Powers Quality of Life Index (QLI) was completed by both groups before, immediately after, and 1 month after the intervention. For the study group participants and their families, 60-min sessions of hope-promoting interventions based on religious beliefs were held twice a week for 3 weeks. Independent t, repeated measures analysis of variance (ANOVA), Chi-square, Mann-Whitney, and Fisher's exact tests were adopted for data analysis. Results: The mean (standard deviation) overall QOL score in the area of satisfaction significantly increased in the study group, compared to the controls, immediately [70.7 (8.5) vs. 59.2 (12.5)] and 1 month after the intervention [75.2 (7.4) vs. 59.4 (12.9)] (P < 0.05). There was also a similar difference between the two groups in the area of importance immediately [73.6 (5.8) vs. 65.7 (7.5)] and 1 month after the intervention [76.3 (8.1) vs. 66.8 (8.5)] (P < 0.05). Conclusions: Hope-promoting intervention based on religious beliefs is a useful method for improving QOL in patients with CHF.